2010
DOI: 10.1186/1472-6823-10-7
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of sitagliptin in clinical studies: a pooled analysis of data from 10,246 patients with type 2 diabetes

Abstract: BackgroundIn a previous pooled analysis of 12 double-blind clinical studies that included data on 6,139 patients with type 2 diabetes, treatment with sitagliptin, a dipeptidyl peptidase-4 (DPP-4) inhibitor, was shown to be generally well tolerated compared with treatment with control agents. As clinical development of sitagliptin continues, additional studies have been completed, and more patients have been exposed to sitagliptin. The purpose of the present analysis is to update the safety and tolerability ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
168
2
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(191 citation statements)
references
References 46 publications
16
168
2
2
Order By: Relevance
“…41 However, a recent safety meta-analysis evaluated the general safety and tolerability profile of sitagliptin from more than 10,000 patients with type 2 DM. 53 The incidence of infections was no different than with comparators. There were no between-group differences using the terms nasopharyngitis, bronchitis, and urinary tract infection.…”
Section: Modulating the Incretin System In Type 2 Dmmentioning
confidence: 93%
See 1 more Smart Citation
“…41 However, a recent safety meta-analysis evaluated the general safety and tolerability profile of sitagliptin from more than 10,000 patients with type 2 DM. 53 The incidence of infections was no different than with comparators. There were no between-group differences using the terms nasopharyngitis, bronchitis, and urinary tract infection.…”
Section: Modulating the Incretin System In Type 2 Dmmentioning
confidence: 93%
“…There were no between-group differences using the terms nasopharyngitis, bronchitis, and urinary tract infection. 53 Bruce et al 51 recently reported the results of a metaanalysis to evaluate the safety and tolerability of exenatide and included 11 comparator-controlled clinical trials. Data from 2251 exenatide-treated patients and 1603 comparator-treated patients were reviewed.…”
Section: Modulating the Incretin System In Type 2 Dmmentioning
confidence: 99%
“…Further investigations are needed to confirm whether better glycemic control by using sitagliptin with or without other oral hypoglycemic agents can improve pre-existing atheroma and thus prevent major cardiovascular events [19][20][21][22][23][24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…They are linagliptin, sitagliptin, vildagliptin, saxagliptin, and alogliptin (13,20,21). In humans, the approved compounds are generally well tolerated and demonstrate various degrees of efficacy in treating type 2 diabetes at recommended doses, sug-gesting that inhibition of DPP-IV activity represents a desirable therapeutic approach for type 2 diabetes (13,(22)(23)(24)(25). However, adverse effects such as nausea, common cold-like symptoms, and pancreatitis have been reported for approved DPP-IV inhibitors (25).…”
mentioning
confidence: 99%
“…In humans, the approved compounds are generally well tolerated and demonstrate various degrees of efficacy in treating type 2 diabetes at recommended doses, sug-gesting that inhibition of DPP-IV activity represents a desirable therapeutic approach for type 2 diabetes (13,(22)(23)(24)(25). However, adverse effects such as nausea, common cold-like symptoms, and pancreatitis have been reported for approved DPP-IV inhibitors (25). Most of the small molecules are competitive reversible inhibitors with different degrees of selectivity toward other family members of prolyl peptidases such as DPP-VIII and DPP-IX.…”
mentioning
confidence: 99%